1991
DOI: 10.1007/bf00151694
|View full text |Cite
|
Sign up to set email alerts
|

The Soft X-ray Telescope for the SOLAR-A mission

Abstract: The Soft X-ray Telescope (SXT) of the SOLAR-A mission is designed to produce X-ray movies of flares with excellent angular and time resolution as well as full-disk X-ray images for general studies. A selection of thin metal filters provide a measure of temperature discrimination and aid in obtaining the wide dynamic range required for solar observing. The co aligned SXT aspect telescope will yield optical images for aspect reference, white-light flare and sunspot studies, and, possibly, helioseismology. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
329
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 968 publications
(335 citation statements)
references
References 15 publications
5
329
0
1
Order By: Relevance
“…Reeves & Warren (2002) modeled the post-flare arcade of the Bastille-day flare on 2000 July 14 by launching 500 loops, each starting 4s after the previous loop. Instead of modeling the heating process, a scaling law was used to evolve plasma temperature and density from given initial values, which were adjusted to best fit the soft X-ray and EUV 195 Å light curves observed by Soft X-ray Telescope (SXT; Tsuneta et al 1991) and TRACE, respectively. Warren (2006) ran a 1D hydrodynamic simulation to model the Masuda flare on 1992 January 13 (Masuda et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Reeves & Warren (2002) modeled the post-flare arcade of the Bastille-day flare on 2000 July 14 by launching 500 loops, each starting 4s after the previous loop. Instead of modeling the heating process, a scaling law was used to evolve plasma temperature and density from given initial values, which were adjusted to best fit the soft X-ray and EUV 195 Å light curves observed by Soft X-ray Telescope (SXT; Tsuneta et al 1991) and TRACE, respectively. Warren (2006) ran a 1D hydrodynamic simulation to model the Masuda flare on 1992 January 13 (Masuda et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, this is an oversimplification of the magnetic field. However, the thermal response of the SXT is strongly biased towards the hotter temperatures, in the range of temperatures being discussed here [Tsuneta et al, 1991], suggesting that the observed increase in temperature with height is not due to geometrical effects along the line of sight. Thus the energy must either be preferentially deposited high in the corona or larger (and therefore higher) loops must have higher maximum temperatures at their apex.…”
Section: Heating Of the Quiet Coronamentioning
confidence: 69%
“…This is possible because of the regular collection of "dark frames" as part of the normal op- Vignetting: Off limb observations of the quiet Sun with SXT requires the analysis of low signal-to-noise data taken off-axis. In such circumstances, vignetting (i.e., the off-axis variation of the telescope effective area) may be nonnegligible [see Tsuneta et al, 1991]. This is taken into account by applying an empirically derived vignette correction to the data used in this study.…”
Section: Appendix: Data Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray and microwave observations can provide information on eruptions close to the solar surface, which is difficult to obtain from coronagraphic observations. After the advent of the Yohkoh/Soft X-ray Telescope (SXT, Tsuneta et al 1991) and the Nobeyama radioheliograph (Nakajima et al 1994), it has become possible to study the near surface manifestations of CMEs in detail. Recent studies have shown that X-ray emission can originate from an arcade formed beneath the erupting filament (Hanaoka et al 1994), the filament itself (McAllister et al 1992) and from the CME frontal structure (Gopalswamy et al 1996(Gopalswamy et al , 1997a.…”
Section: Introductionmentioning
confidence: 99%